KEWIBAWAAN PEMIMPIN DALAM MEMBANGUN BUDAYA POSITIF DI SEKOLAH - Nurmalasari, Nurmalasari; Duhana, Tara; Mahdum, Mahdum; Azhar, Fadly; Dahnilsyah, Dahnilsyah (STKIP Pesisir Selatan, 2025)
Objective: This study aims to analyze how authoritative leadership contributes to the development of a positive school culture through a systematic review of national and international studies. Methods: A Systematic Literature Review (SLR) was conducted by selecting ten relevant articles based on predefined inclusion criteria. The analysis involved data extraction, thematic categorization, and narrative synthesis to identify key patterns across the literature. Results: The synthesis reveals that authoritative leadership is characterized by moral integrity, trust-building capacity, exemplary conduct, and consistent leadership practices. Five major themes emerged: (1) leadership grounded in integrity and trust; (2) strengthening positive culture through pedagogical and collaborative practices; (3) the role of leadership in establishing fairness and positive discipline; (4) principal role modeling as a driver of values and character; and (5) authoritative leadership as a guide for school vision, values, and transformation. Findings indicate that authoritative leaders help create a safe, harmonious, and supportive environment through moral example and value reinforcement. Novelty: This study provides an updated thematic framework on the strategic role of authoritative leadership in building positive school culture, offering holistic insights relevant for strengthening leadership practices in the educational context.